Stability analysis of load frequency control for power systems with interval time-varying delays - Sun, Yanyan; Bo, Xiaoting; Duan, Wenyong; Lu, Qun (Frontiers in Energy Research, 2023)
This paper investigates stability problem of load frequency control (LFC) for networked power systems with interval time-varying delays. The two categories of time delays, the lower bound being zero and non-zero, are respectively considered. The systems can be described as time delay systems of load disturbances. Firstly, an augmented Lyapunov-Krasovskii functional (LKF) is constructed. Some delay-dependent non-integral terms and single integral terms are extra introduced to make full use of the information on the system state variables and the time-varying delays. Secondly, to overcome the problem of nonlinear inequalities caused by the augmented LKF, the nonlinear inequalities are converted into the linear matrix inequalities (LMI) by applying the new negative definite inequalities equivalence transformation lemma, which can be solved easily by MATLAB LMI-tool box. A new stability criterion is presented by applying the Lyapunov stability theory. The stability criterion are less conservative than some existing literature, which further improves the stability margin for the power systems based on LFC. Finally, some numerical examples are given to show the effectiveness of the proposed method and the superiority of the results.